The effects of urbanisation on the availability of medical plants at Malamulele Area, Limpopo Province, South Africa - Shibambu, Nyiko Faith (My University, 2024)
Medicinal plants are important to humanity and continue to be used worldwide as a source of food and basic healthcare. However, most of them are under threat of extinction. This was prompted by several negative factors contributing to the extinction of these [Medicinal] plants. These factors are, among others, demarcated to habitat loss, population increase, urbanisation and threats brought by climatic change. The purpose of this study was to ‘explore the effects of urbanisation on the availability of medicinal plants in Malamulele area of Limpopo Province, South Africa (SA). From a qualitative standpoint, this study employed exploratory research design. This study used non-probability sampling, also known as purposive sampling, and snowball sampling and to select twenty participants. These twenty participants comprised five traditional health practitioners and fifteen community members. Further, the study employed semi-structured In-Depth Interviews (IDIs) and documentary studies to collect data. Additionally, the study was underpinned by the Afrocentric Theory and Dependency Theory. For data analysis, the Spiral data was adopted to organise data and identify study themes aligned to the aim and objective of this study. The findings of this study highlight that the availability of medicinal plants in the Malamulele were threatened by urban development, leading to their extinction. All the participants reached a consensus that the ‘indigenous medicinal plants’ in Malamulele suffer a great loss due to urbanisation and lack of implementation of available conservation methods to prevent them from possible extinctions. The study found that these conservation methods are improperly implemented or not implemented at all. Again, it was found that the discovered rapid loss of these plants might negatively affect future preservations and protections. Apparently, urbanisation contributes to the witnessed decreases of natural resources, and medicinal plants are not immune. It is also shared that although the majority of Malamulele residents still heavily rely on positive use of medicinal plants such as sources of food, herbalism, medicinal activities, primary health care needs and therapeutic values; nevertheless, residents are often unable to protect these plants from threats imposed by urbanisation. This study concludes and recommends that lack of information regarding the importance of these plants, necessary conservation methods and awareness should be urgently looked at by relevant stakeholders in this sector. Therefore, this study vi reveals that indigenous people and Collins Chabane Local Municipality (CCLM) should take actions to protect these plants from extinctions. For Malamulele residents to achieve this, biodiversity knowledge and management skills are urgently required; also, responsive interventions should be introduced to better local current situations in the selected rural areas of Malamulele.
Thesis (M.A. (Anthropology)) -- University of Limpopo, 2024
Keywords: Traditional medicine; Medicinal plants; Indigenous plants extinction; Plants conservation; Urbanisation; Malamulele area; Limpopo Province; South Africa; Medicinal plants; Primary health care; Urbanization -- South Africa -- Limpopo; Plant conservation